Predvidevanje nelinearnega lezenja izdelkov - Spoormaker, Jan (Strojniški vestnik, 2007)
Based on an example of the non-linear creep deformations of an air inlet, thispaper demonstrates modern capabilities in the FEA modeling of complex 3D visco-elastic deformations in relation to the design of plastic products. The importance of such capabilities for designing complex plastic components is discussed. Because commercial FEA packages do not yet render these capabilities "off the shelf", the non-linear visco-elasticity model is incorporated through a user subroutine. The specifics of the constitutive model and its numerical implemen-tation are outlined for the case of implementation in the commercial FEA package MSC.MARC.
Keywords: lezenje; nelinearna dinamika; napetosti; analiza končnih elementov; polimeri